Iron-tracking strategies: Chaperones capture iron in the cytosolic labile iron pool - Philpott, Caroline C.; Protchenko, Olga; Wang, Yubo; Novoa-Aponte, Lorena; Leon-Torres, Andres; Grounds, Samantha; Tietgens, Amber J. (Frontiers in Molecular Biosciences, 2023)
Cells express hundreds of iron-dependent enzymes that rely on the iron cofactors heme, iron-sulfur clusters, and mono-or di-nuclear iron centers for activity. Cells require systems for both the assembly and the distribution of iron cofactors to their cognate enzymes. Proteins involved in the binding and trafficking of iron ions in the cytosol, called cytosolic iron chaperones, have been identified and characterized in mammalian cells. The first identified iron chaperone, poly C-binding protein 1 (PCBP1), has also been studied in mice using genetic models of conditional deletion in tissues specialized for iron handling. Studies of iron trafficking in mouse tissues have necessitated the development of new approaches, which have revealed new roles for PCBP1 in the management of cytosolic iron. These approaches can be applied to investigate use of other nutrient metals in mammals.